(untitled) (Research, Society and Development, 2021)
Introduction: Aids is a disease characterized by a deficiency of the immune system and which, in the past, brought great social stigma and low life expectancy to its patients. Associated with the increase in life expectancy, new health issues emerged among this population related to both aging and the vulnerability of HIV, which resulted in the inherent complexity of the pharmacological management of these diseases concomitant with antiretroviral therapy and their inadvertent iatrogenic risks, thus highlighting the interaction between Ritonavir. Method: A literature review was carried out in the online databases of the Virtual Health Library (VHL), using the descriptors: "Iatrogenic Cushing’s syndrome" AND “HIV” from 2011 to 2021. Results and discussion: 24 articles found, 2 were literature reviews with an approach to the relationship between HIV and iatrogenic Cushing’s syndrome and 22 corresponded to case reports that had based on patients with HIV in association with chronic diseases developed by age, with emphasis on musculoskeletal, respiratory and rheumatological disorders. Due to this combination, polypharmacy was applied, with the use of corticosteroids and antiretroviral therapy with Ritonavir the convergent pharmacological factor among all cases, as well as the main clinical manifestation: Cushing’s Syndrome. Conclusion: It was noted that the use of exogenous glucocorticoids, like Triamcinolone, Fluticasone and Budesonide stand out, which interact with Ritonavir, in patients taking antiretroviral therapy for HIV can induce clinical presentations of Cushing’s syndrome.